An overview of cleaner fish use in Ireland. Issue 6 (21st November 2017) - Bolton‐Warberg, M
Abstract: Sea lice infestations represent one of the most significant challenges facing the salmon farming industry, giving rise to lost production, additional costs of treatment and potential negative interactions with wild stocks. At present, cleaner fish, which actively remove lice from salmon, are an effective, biological, long‐term option which has been adopted by many countries. In Ireland, several key studies were conducted in the 1990s on the use of wild‐caught wrasse (corkwing, goldsinny and rock cook) as cleaner fish in experimental and commercial scale trials. More recently, the National University of Ireland Galway (NUIG), at their marine research facility in Carna (CRS), has undertaken applied research on ballan wrasse and lumpsucker. Currently, CRS is providing lumpsucker juveniles and research and development for the Irish salmon industry with support from BIM (Ireland's Seafood Development Agency) and Marine Harvest Ireland. There is a large amount of research currently being carried out in this area in all countries that are utilizing cleaner fish technology. The current focus in Ireland is the development of a native lumpsucker broodstock to facilitate its sustainable production. The aim of this article was to provide an overview of the research, challenges and use of cleaner fish in Ireland.